PTU-001 Polyps at difficult and high risk location: video series to ilustrate the principles of assessment and resection. (22nd June 2015) - Kurup, AK; Bhattacharyya, R; Chedgy, F; Kandiah, K; Bhandari, P
Abstract : Introduction: One of the factors which make the removal of a polyp challenging is its location in the GI tract. We will present a series of video clips of polyps located in difficult locations to demonstrate the challenges facing the endoscopist and discuss the strategies to circumvent the problem. Three types of polyps are discussed in this abstract: 1. Polyps involving the dentate line 2. Polyps involving the ileo-caecal valve and terminal ileum and 3. Polyps involving the appendiceal orifice. Method: Information regarding the nature, location, procedure, recurrence, complication and need for surgery was obtained from a prospective database of polyps more than 2 cm removed between 2010 and 2014. Results: 1. Polyp involving the dentate line: Access to these polyps is very difficult. A rich sensory supply of the distal squamous epithelium, difficulty in identifying the distal edge of the polyp and the rich vascular supply in this region makes it challenging. Twelve cases [n = 12] underwent endoscopic resection. The size ranged from 12 mm–150 mm occupying 25% to 80% of the circumference. Laterally spreading tumour –Granular [n = 10] and two were sessile [1s and 1s/2c, n = 2]. 1. Polyp involving the ileo –caecal valve. Here the challenges include difficult access, identifying the margins, ileal extension and risk of perforation. Seven polyps, 30 mm–60 mm in size and involving the ileo- caecal valves were removed endoscopically. LST –G [5], 1s [1] and SSA [1]. 1. Polyp involving the appendicular orifice Decision to resect these polyps should be weighed against the risk of perforation since these polyps could extend into the appendicular canal. Nine cases of polyp involving the appendicular orifice were resected endoscopically with size ranging from 20 mm -100 mm. Six were LST –G[[7]sessile polyp [2]. Histology of the resected polyps was as follows. TVA with LGD [21], TVA with foci of HGD [2], sessile serrated adenoma [4], tubular adenoma with intra mucosal cancer [1], Tubular adenoma [1]. Conclusion: Polyps located at the appendicular orifice and ileo -caecal valve have traditionally been managed with right hemicolectomy and polyps at the dentate line with TAR/TEMS. Our data shows that an expert endoscopist can resect these polyps with good clearance and avoid surgery. This makes a case for referral of these polyps to an expert centre. Disclosure of interest: None Declared.